Transforming Oncology: Cutting-Edge Developments In Radionuclide Therapies - Sayed Manzer Tasfiya; Shabaray. R.A; Nayak A Lathika (Asian Journal of Pharmaceutical Research and Development, 2024)
Main objective of this study was to list out the recent advancement in radionuclide therapy.Cancer rates are increasing globally at a rapid pace. This trend is influenced by a combination of factors, including the aging and expansionof the population, as well as shifts in the prevalence and distribution of key cancer risk factors.Current cancer treatments, such as surgery and external beam radiotherapy, become less effective once a tumor has spread. Targeted radionuclide therapy (TRT) uses radio-labeled biologics or other carriers to precisely deliver a cytotoxic dose of radiation to inoperable or metastatic cancer, emitting Auger electrons, β-particles, or α-particles.β-particle-emitting RPT agents have highly promising clinical and preclinical preliminary results with RPT agents using other α-particle-emitting radionuclides has reignited interest in RPT.Recent advancements in radionuclide therapies have shown promising results in various cancers. Astatine-211 (211At) has demonstrated potential in treating paraganglioma, acute leukemia, and thyroid cancer. 225Ac-DOTATATE has shown promise for gastroenteropancreatic neuroendocrine tumors. Bismuth-213 (213Bi) and Lead-212 have also shown positive results in treating different cancers, including small lung cancer. Boron neutron capture therapy (BNCT), recently FDA-approved, has improved outcomes in head and neck cancer. Additionally, nanomaterials are being used to deliver radionuclides more effectively, enhancing treatment precision and patient outcomes. In conclusion there is a wide advancement in radionuclide therapy in today’s world and preparing for the future therapies. Radionuclide therapy is a door for the multitude of cancers and thus is a potential treatment option for those with advanced cancers and failed established therapeutics.